Pharmacokinetics of Deutetrabenazine and Tetrabenazine: Dose Proportionality and Food Effect. Issue 6 (10th October 2020) - Schneider, Frank; Stamler, David; Bradbury, Margaret; Loupe, Pippa S.; Hellriegel, Edward; Cox, Donna S.; Savola, Juha‐Matti; Gordon, Mark Forrest; Rabinovich‐Guilatt, Laura
Abstract: Deutetrabenazine (Austedo, Teva), an approved treatment of chorea in Huntington's disease and tardive dyskinesia in adult patients, is a rationally designed deuterated form of tetrabenazine. Two studies assessed the pharmacokinetics and safety of deutetrabenazine compared with tetrabenazine, and the effects of food on absorption of the deuterated active metabolites, α‐dihydrotetrabenazine (α‐HTBZ) and β‐dihydrotetrabenazine (β‐HTBZ). One study was an open‐label 2‐part study in healthy volunteers; the first part included a crossover single dose of two 15 mg candidate deutetrabenazine formulations in fed and fasted states compared with tetrabenazine 25 mg in the fasted state, and the second part included single and repeated dosing of the commercial formulation of deutetrabenazine (7.5, 15, and 22.5 mg) compared with tetrabenazine 25 mg. The second study was an open‐label 5‐way crossover study in healthy volunteers (n = 32) to evaluate relative bioavailability of 4 dose levels of the commercial formulation of deutetrabenazine (6, 12, 18, and 24 mg) with a standard meal and 18 mg with a high‐fat meal. Both studies confirmed longer half‐lives for active metabolites and lower peak‐to‐trough fluctuations for the sum of the metabolites (total [α+β]‐HTBZ) following deutetrabenazine compared with tetrabenazine (3‐ to 4‐fold and 11‐fold, respectively) in steady‐state conditions. Deutetrabenazine doses estimated to provide total (α+β)‐HTBZ exposure comparable to tetrabenazine 25 mg were 11.4‐13.2 mg. Food had no effect on exposure to total (α+β)‐HTBZ, as measured by AUC. Although the total (α+β)‐HTBZ Cmax of deutetrabenazine was increased by ≈50% in the presence of food, it remained lower than that of tetrabenazine.